PRAKTEK SEWA KEPEMILIKAN AKUN DRIVER TRANSPORTASI ONLINE DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Kartini, Kartini; Kencana, Ulya; isa, legawan (Muamalah, 2018)
ABSTRACT One form of human activity in bermuamalah one of which is a rent, which in Arabic is termed al-ijaarah means that the benefits must be received by someone for the services that have been given. The rental activity (Ijarah) that occurs in Palembang city is the rental of an online transportation driver account. Based on the results of observations, one of the leases currently taking place in the city of Palembang, namely the lease to rent an account for transportation drivers online. Starting from these problems, the main issues that will be discussed include how the practice of leasing ownership of an online transportation Driver Account in Palembang, and how to review the Islamic Economics Law on the lease agreement for the ownership of the Transport Driver Account in Palembang. This research is a field research (Field Riserch), where all data both primary data and secondary data are taken from the results of interviews and documents that are reading books and other written info related to the problem under study. To analyze using qualitative methods which are then taken a conclusion. The results of the study, concluded that the Rental Practice of Account Ownership Driver Online Transportation in Palembang City is not in accordance with Islamic sharia because it contains elements of fraud (Gharar). Referring to PT GOJEK INDONESIA regulation No. 14 which reads "Falsifying data and manipulating accounts; like different data on the application, using a broken account partner, falsifying the original data (KTP / SIM / SKCK) using a hijacked account, etc. ". Thus the lease to rent an online transportation driver account is a violation and is prohibited. Keywords: Leasing, Driver Account, Sharia Economic Law